Pembingkaian Berita Media Online - Achmad Yaman; Sukijan Sukijan (STID DI AL-HIKMAH, 2016)
This study aims to find out about special framing and republika detik.com online. The study also want to find a complete structure of the news media. This type of research is qualitative descriptive analysis using models Zongdang framing Pan and Gerald M Kosicki. The results showed differences in the framing of both media, the choice of title and content related news caricatures of the Prophet Muhammad. Republika Online Detik.com and often does not include source citations and less attention to the structure of 5W + 1H, so that the news published be less than perfect. Detik.com news looked caricatures of the Prophet Muhammad do not need to be inflated exaggerated because it is not in accordance with freedom of expression. Republika it looked online magazine with a cover drawing caricatures of the Prophet Muhammad is a large store of harassment against Muslims.